The Aporia of Power: Crisis and the Emergence of the Corporate State - Kapferer, Bruce (Social Analysis, 2010)
The argument focuses on the corporate state as an increasingly significant political assemblage that has enabled new configurations of power with related social effects. Here the discussion proceeds from Karl Polanyi's thesis in The Great Transformation. A critical idea that Polanyi pursued related to the state production of economism and individualism, which prepared the ground for the expansion of capital in its globalizing form. The essay develops this idea, indicating that the nationalist capitalism of the state led to a radical change in the political and social orders of states, gradually giving rise to the corporate state assemblage. The emphasis here is on the corporate state as a socio-political order that places radically distinct structural dynamics into impossible conjunction, leading to progressively disastrous social effects concerning poverty and the emergence of new configurations in which war and violence take specific shapes.
Anthropology; Sociology
Keywords: Great Transformation; The (Book); bureaucratic processes; corporate state; crisis; economism; globalization; individualism; nation-state; poverty; power (social sciences); reterritorialization; violence; war; war machine

Polanyian meditations on economy and society: a review of 'Market society: the great transformation today' - Dale, Gareth (Dialectical anthropology, 2010)
Anthropology
Keywords: book review; cultural ethnography; economic anthropology; market economy; society

Building the Human Economy Together - Hart, Keith; Laville, Jean-Louis; Cattani, Antonio (The Human Economy. A Citizen’s Guide, 2010)
KM: We want to bring to the attention of English readers some currents of economic theory and practice that have flourished in non-Anglophone countries over the last two decades, particularly in France, Brazil, Hispanic America and Scandinavia. To these we have added significant work by English-speaking authors that was sidelined during neoliberalism’s heyday and deserves to find a wider audience now. We have brought these strands of new thinking together under the umbrella concept of ‘the human economy’ which refers to an emphasis both on what people do for themselves and on the need to find ways forward that must involve all of humanity somehow.
Anthropology
Keywords: human economy; solidarity economy